A new method used in laparoscopic hysterectomy for uterine manipulation: uterine rein technique - Boztosun, Abdullah; Atilgan, Remzi; Pala, Sehmus; Olgan, Safak (Taylor & Francis Inc, 2018)
The aim of this study is to define a new method of manipulating the uterus during laparoscopic hysterectomy. A total laparoscopic hysterectomy (TLH) with the newly defined technique was performed in 29 patients between July 2016 and July 2017. In this new technique, the uterus was bound from uterine corpus and fundus like a bridle with polyester tape, to allow abdominal manipulation. The technique was successfully performed at the first attempt in 93.1% of cases. It was repeated in two cases (6.9%) since the polyester tape departed away from the uterus at the first attempt. The mean application time was 11.2 min. The vaginal manipulator was not required in any of the cases. There were no intraoperative complications. In conclusion, this method has the advantages of not requiring any vaginal manipulator, reducing the number of people required during operation, permitting a near maximum manipulation of the uterus in all three dimensions, and giving the control of these manipulations directly to the surgeon. On the other hand, the technique also has some inadequacies which should be discussed and improved on in the future. IMPACT OF STATEMENT What is already known on this subject? In a laparoscopic hysterectomy, manipulation of the uterus is essential for anatomical dissection of the regions and completion of the operation without complications. An ideal uterine manipulator is defined as inexpensive, as convenient, fast and suitable for injecting solutions, removing the need for an assistant and most importantly offering the most suitable range of motion. In this study, we describe a new and different technique (rein technique) allowing the abdominal manipulation of the uterus in a laparoscopic hysterectomy and discuss the advantages and disadvantages of this method. What do the results of this study add? The procedure was easily accomplished in most patients. We did not need to use an extra uterine manipulator in any of the cases. What are the implications of these findings for clinical practice and/or further research? In conclusion, the rein technique of uterine manipulation is effective and safe.
Keywords: Laparoscopic hysterectomy; uterine manipulator; uterine rein technique